2019
DOI: 10.1177/0972150919837079
|View full text |Cite
|
Sign up to set email alerts
|

On the Causal Dynamics Between Economic Growth, Trade Openness and Gross Capital Formation: Evidence from BRICS Countries

Abstract: The present study investigates the long-run association and direction of causality among economic growth, trade openness and gross capital formation in Brazil, Russia, India, China and South Africa (BRICS) nations. This article applied autoregressive distributed lag (ARDL) and vector error correction model to examine the long-run association and casual relationship among the competing variable. The ARDL bound test results indicate long-run relationship among economic growth, trade openness and gross capital fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 51 publications
6
34
2
1
Order By: Relevance
“…In other words, TO shows a significant effect on economic development, endorsing the tradeinduced growth hypothesis. Our findings support the prevailing literature and empirical confirmation presented by a case study of SADC nations by Maune (2019), a study related to Turkey by (Alsamara, Mrabet et al 2019), and a study of BRICS economies by Rani and Kumar (2019). Likewise, some studies contrasted with our findings, such as Olaifa et al (2013) and .…”
Section: The Long-run Impact Of Selected Macroeconomic Variables On Economic Developmentsupporting
confidence: 92%
“…In other words, TO shows a significant effect on economic development, endorsing the tradeinduced growth hypothesis. Our findings support the prevailing literature and empirical confirmation presented by a case study of SADC nations by Maune (2019), a study related to Turkey by (Alsamara, Mrabet et al 2019), and a study of BRICS economies by Rani and Kumar (2019). Likewise, some studies contrasted with our findings, such as Olaifa et al (2013) and .…”
Section: The Long-run Impact Of Selected Macroeconomic Variables On Economic Developmentsupporting
confidence: 92%
“…In addition, another important result that has been obtained in the results is that the GDP has significant along with positive impact on financial development of a country. These two aspects are very much related to each other and many studies in the past have confirmed this result (Chen & Lei, 2018;Nguyen, Su, & Nguyen, 2018;Rani & Kumar, 2019). As the GDP of a country increases, different sectors of the country get benefited financially from this increase in GDP and thus the FD is increased.…”
Section: Discussionmentioning
confidence: 72%
“…It is very common that in the long run, more outward-oriented economies are associated with better economic growth (see, for instance, [97][98][99][100][101], among others), and our results support this statement. In the same line, gross fixed capital formation is positively linked to economic growth (as stressed by [102][103][104], among others). On the contrary, inflation rate deteriorates economic growth (the same conclusion was achieved by [105,106], among others).…”
Section: Resultsmentioning
confidence: 92%